1997
DOI: 10.1037/0022-3514.73.5.1038
|View full text |Cite
|
Sign up to set email alerts
|

Pancultural explanations for life satisfaction: Adding relationship harmony to self-esteem.

Abstract: The first part of the study confirmed an additive effect of the newly proposed construct of relationship harmony to self-esteem in predicting life satisfaction across student samples from the United States and Hong Kong. As predicted from the dynamics of cultural collectivism, the relative importance of relationship harmony to self-esteem was greater in Hong Kong than in the United States. In the second part of the study, the independent and interdependent self-construals (H. R. Markus & S. Kitayama, 1991) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
647
10
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(731 citation statements)
references
References 45 publications
58
647
10
8
Order By: Relevance
“…Table 1 provides a summary of these findings. Most of the studies used college student samples and found that self-esteem had a strong positive correlation with Emotional Stability, moderate positive correlations with Extraversion and Conscientiousness, and weak positive correlations with Agreeableness and Openness (Goldberg & Rosolack, 1994;Jackson & Gerard, 1996;Kwan, Bond, & Singelis, 1997;Keller, 1999;Robins, Hendin, & Trzesniewski, 2001). The two studies of adults found a similar pattern of correlations (Costa, McCrae, & Dye, 1991;Pullman & Allik, 1999).…”
Section: Previous Researchmentioning
confidence: 58%
See 1 more Smart Citation
“…Table 1 provides a summary of these findings. Most of the studies used college student samples and found that self-esteem had a strong positive correlation with Emotional Stability, moderate positive correlations with Extraversion and Conscientiousness, and weak positive correlations with Agreeableness and Openness (Goldberg & Rosolack, 1994;Jackson & Gerard, 1996;Kwan, Bond, & Singelis, 1997;Keller, 1999;Robins, Hendin, & Trzesniewski, 2001). The two studies of adults found a similar pattern of correlations (Costa, McCrae, & Dye, 1991;Pullman & Allik, 1999).…”
Section: Previous Researchmentioning
confidence: 58%
“…There is virtually no research on these issues and no clear theoretical basis for making predictions. The only existing relevant studies, Kwan et al's (1997) study of Hong Kong students and Pullman and Allik's (1999) study of Estonian adults, point to the generalizability of the Big Five correlates of self-esteem to non-U.S. populations.…”
Section: Previous Researchmentioning
confidence: 99%
“…For instance, a sense of congruence between self-defining sets of relations (e.g., as a wife and as a daughter-in-law), between one's wish and others' expectation, or between the self and the psychological situation may be crucial to the collectivists' conception of overall well-being. Such possibilities, in turn, call for the urgent need to uncover indigenous components of life satisfaction, such as relationship harmony (Kwan, Bond, & Singelis, 1997), in the more collective-oriented cultures. Second, our findings have tapped into an interesting issue for cross-cultural studies on emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Our second objective was to compare the responses with the RSESboth within and across cultures-with other personality measures and test the external equivalence of the RSES. Previous findings have indicated that scores on the RSES correlate strongly with two of the Big Five dimensions: Neuroticism and Extraversion (Costa, McCrae, & Dye, 1991;Kwan, Bond, & Singelis, 1997;Pullmann & Allik, 2000;Robins, Tracy, & Trzesniewski, 2001). The universality of this relationship has been questioned by an opposing view that self-esteem is a culturally specific construct that only sometimes provides a protective barrier against neuroticism.…”
Section: External Equivalence Of Global Self-esteemmentioning
confidence: 99%